2003
DOI: 10.1017/s0021859603003666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of several germination conditions on total P, phytate P, phytase, acid phosphatase activities and inositol phosphate esters in spring and winter wheat

Abstract: Changes in the wheat phosphatases (phytase-Phy and acid phosphatase-AcPh) and the degradation of their substrates (inositol phosphates esters) during seed germination have been examined in two studies. Germinated grains with high phytate degrading enzymes are of potential interest in the improvement of phosphorus availability in monogastric animals. In the first study, the seeds were soaked for 1 and 14 h and germinated for 3 and 5 days with and without the addition of gibberellic acid (GA3). In the second stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Recently, an interaction between lpa mutations and anthocyanin accumulation and compartmentalization in the kernels of maize lpa mutants was suggested (Badone and others ), which could lead to changes in the attraction of pollinators, signaling with microbes, male fertility, antimicrobial activity, UV protection, and in general the protection from oxidative damage (Winkel‐Shiley ). Phytate are degraded by endogenous phytases which release phosphate and other minerals during seed germination that supports the growth and development of the seedling (Centeno and others ; Hemalatha and others ). Thus, it is anticipated that breeding lpa crops using mutation breeding may seriously hamper seed germination and plant performance, which will ultimately affect yields.…”
Section: Breeding Approaches To Reduce Phytatementioning
confidence: 99%
“…Recently, an interaction between lpa mutations and anthocyanin accumulation and compartmentalization in the kernels of maize lpa mutants was suggested (Badone and others ), which could lead to changes in the attraction of pollinators, signaling with microbes, male fertility, antimicrobial activity, UV protection, and in general the protection from oxidative damage (Winkel‐Shiley ). Phytate are degraded by endogenous phytases which release phosphate and other minerals during seed germination that supports the growth and development of the seedling (Centeno and others ; Hemalatha and others ). Thus, it is anticipated that breeding lpa crops using mutation breeding may seriously hamper seed germination and plant performance, which will ultimately affect yields.…”
Section: Breeding Approaches To Reduce Phytatementioning
confidence: 99%
“…Phytase activity increases significantly during seed germination. In spring and winter wheats, phytase activities increased by 275% and 250%, respectively after germination (Centeno et al 2003). Phytase activity in lentils, broad beans and runner beans reached maximum levels after 8 days of germination, around 10-fold (Kyriakidis et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that phytases with broad substrate specificity are better suited for animal nutrition purposes than phytases with narrow substrate specificity [39] . A widely used method for estimation of phytase activity is to incubate the sample with phytate and estimate the phytase activity by determining released inorganic phosphorus, which can also be performed on crude extracted phytases [8] , [27] , [30] , [40] . This method was employed in all the experiments in the current study.…”
Section: Discussionmentioning
confidence: 99%